Monotonicity of the Ratio of the Power and Second Seiffert Means with Applications - Zhen-Hang Yang; Ying-Qing Song; Yu-Ming Chu (Abstract and Applied Analysis)
We present the necessary and sufficient condition for the monotonicity of the ratio of the power and second Seiffert means. As applications, we get the sharp upper and lower bounds for the second Seiffert mean in terms of the power mean.